Is the dating of short tree-ring series still a challenge? New evidence from the pile dwelling of Lucone di Polpenazze (northern Italy). (September 2020) - Capano, Manuela; Martinelli, Nicoletta; Baioni, Marco; Tuna, Thibaut; Bernabei, Mauro; Bard, Edouard
Abstract: Short tree-ring series are a recurrent problem in dendroarchaeological studies because they are difficult to match against site and reference chronologies. Young wood posts discovered at the Early Bronze Age pile-dwelling site of Lucone D (Brescia, Italy) show tree-ring series not exceeding 40 rings. Dendrochronological analysis allowed us to cross-match 10 short series, which fail to find a cross-match against the site chronology and the regional GARDA1 chronology. Their precise dating, however, would invite new scenarios to better understand both the construction activity and the woodland management practices of ancient populations. Here, we examine the dating of these posts and speculate on young wood use in the context of pile dwellings. In order to precisely 14 C date the subchronology of the 10 posts, we isolated random annual rings from two posts. Then, using wiggle-matching, the annual 14 C measurements of the young woods were dated against a new absolute annual calibration curve (spanning 136 years from −2065 to −1929), which we built by measuring the 14 C content in absolutely-dated subfossil trees. An offset of ca. 25 years between annual 14 C values of the Aix-BA and IntCal13 curves was found, probably due to an analytical bias of the previous low-resolution 14 C measurements of IntCal13. A calibration curve at high resolution (i.e. annual) proved to be extremely important for high-precision dating of short tree-ring series. The analysis of short tree ring series from the Lucone D settlement allowed to make assumptions about the use of young woods for either a fourth and final construction phase preceding the abandonment of the village, or for renovating ancient structures during the last stages of the settlement's life. Highlights: Short tree-ring sequences are dated using dendrochronology and 14 C dating. Wiggle-matching is performed on annual rings, measured at high-resolution. A new calibration curve is built at annual resolution for the Bronze Age. The use of the new 14 C calibration curve avoids a 40 years dating bias. New evidences for the forest management of an ancient population emerged.